Efficiency of Zakat and Infaq/Sedakah Fund Management in BAZNAS: A Comparative Study for 2021-2022: Efisiensi Pengelolaan Dana Zakat dan Infak/Sedekah di BAZNAS: Studi Komparatif Tahun 2021-2022 - Waidi Salaman, Cholis; Rosidi, Ach (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2024)
The management of zakat and infaq/alms funds in philanthropic institutions faces significant challenges in achieving optimal efficiency. This study aims to evaluate the efficiency of fund management in the National Amil Zakat Agency (BAZNAS) from 2021 to 2022. Quantitative research methods were used with comparative analysis of financial ratios, including operational efficiency ratio, fund distribution ratio, fund growth ratio, and ratio of administrative costs to total funds. The results showed an increase in efficiency with the operational efficiency ratio rising from 70% to 75%, the fund distribution ratio increasing from 70% to 75%, and a decrease in the administrative cost ratio from 5% to 4%. These findings indicate that BAZNAS succeeded in improving the effectiveness of fund management, which had a positive impact on fund distribution. The implications of this study suggest increased adoption of technology and management systems as well as periodic evaluation to maintain and improve efficiency in the future.